PERAN GURU DALAM MENINGKATKAN NILAI NASIONLISME SISWA MELALUI PEMBIASAAN LAGU-LAGU NASIONAL - Rita waroka; Dedi Romli Triputra; Yasin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Researchers use a qualitative approach using a phenomenological approach. The research was conducted from May 2024 to July 2024. The subjects in this study were students and teachers. Data collection techniques through passive participant observation, semi-structured interviews and documentation. Data validity uses source and data triangulation. Data analysis uses miles and huberman theory using data collection steps, data reduction, data presentation and drawing. The results of the study of the role of teachers in increasing students' nationalism values ​​through the habituation of national songs, teachers invite students to carry out ceremonial activities, singing national songs on Saturday mornings and after school which are carried out routinely to instill a sense of love for the homeland, appreciate the services of heroes and be willing to sacrifice for the nation and state. Obstacles faced in the habituation of national songs, through students' understanding in knowing the title of the national song, understanding in understanding the creator of the national song and understanding in mastering the lyrics of the national song.